2008
DOI: 10.1590/s0034-72992008000100018
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo entre o aproveitamento escolar de alunos de escola de 1º grau e teste de inibição de emissões otoacústicas transientes

Abstract: School learning can be hampered if there are defects on the central auditory process. Since those with auditory deficiency can be rehabilitated, it is fundamental that we identify them. Otoacoustic emissions test has low cost and operational ease. Study design: clinical and experimental. Aim: to study the relationship between school learning and transient otoacoustic emission suppression by contralateral stimuli. Material and Methods: 39 individuals, from 7 to 12 years of age were evaluated, 19 (48.7%) with go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
2
Order By: Relevance
“…Studies on preterm-born children assessed when in their school age showed worse performance in auditory processing 15 and also a reduced suppression effect. 14 Thus, it is suggested that, over time, the weakest suppression effect observed in preterm-born children's group could be associated with a difficulty in the hearing ability for sound source localization and performance in auditory discrimination tasks, as well as with auditory processing disorders, 16 , 17 , 18 learning problems, 19 , 20 and speech. 21 Therefore, the identification of a minimal or non-inhibitory effect on newborns would act as a marker for risk of hearing disorder and its consequences, suggesting a closer monitoring of this population.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on preterm-born children assessed when in their school age showed worse performance in auditory processing 15 and also a reduced suppression effect. 14 Thus, it is suggested that, over time, the weakest suppression effect observed in preterm-born children's group could be associated with a difficulty in the hearing ability for sound source localization and performance in auditory discrimination tasks, as well as with auditory processing disorders, 16 , 17 , 18 learning problems, 19 , 20 and speech. 21 Therefore, the identification of a minimal or non-inhibitory effect on newborns would act as a marker for risk of hearing disorder and its consequences, suggesting a closer monitoring of this population.…”
Section: Discussionmentioning
confidence: 99%
“…Such absence occurred in the researched individuals, evidencing the importance of researching teenagers' hearing, even when they do not refer auditory symptoms or complaints, because there are risks factors in this age group and there are other facts related to this absence of suppression factor. For instance, there is disorder on school performance 25 , considering the importance of medial olivocochlear system integrity for learning.…”
Section: Discussionmentioning
confidence: 99%
“…Acredita-se que o ruído ativa o feixe olivococlear medial, que modula a atividade sensorial periférica, atenuando a percepção do ruído e salientando a percepção de pequenas mudanças acústicas rápidas características dos sons de fala [17]. Entretanto, alguns pesquisadores relataram falha no mecanismo de ação do feixe olivo-coclear medial em indivíduos com distúrbios do processamento auditivo e de aprendizagem [18,19,20,21], sugerindo alterações no processamento neural não apenas na via auditiva ascendente do sistema nervoso auditivo central (SNAC), mas também na via descendente.…”
Section: Introductionunclassified
“…Sabe-se que a via auditiva eferente (descendente) possui um papel importante no desempenho da captação do sinal acústico na presença de ruído e na atenção seletiva, mas pouco foi estudado sobre sua relação com as alterações auditivas e de aprendizagem, principalmente em regiões mais altas do sistema, como as regiões geradoras do potencial cognitivo P300 [17,18,19,20,21,22].…”
Section: Introductionunclassified